REDESCRIPTION OF FROGHOPPERS, Cercopis intermedia Kirschbaum, 1868 (HOMOPTERA: CERCOPIDAE) FROM ERBIL GOVERNORATE KURDISTAN REGION– IRAQ - Mudhafar I. Hamad; Nabeel A. Mawlood; Abdul-Qadir S. Khidhir (Zanco Journal of Pure and Applied Sciences, 2020)
The present work includes a details description of froghoppers, Cercopis intermedia Kirschbaum,1868 from Erbil Governorate Kurdistan Region– Iraq. The specimens were collected from the wheat field and the flower of some weeds during the period of March to June- 2018. The taxon is easily distinguishable, where the antenna dark brown, filliform, flagellum is the smallest, 0.8 times as long as pedicel, basal body of the flagellum conic with an arista nearly 5 times longer than pedicel. Forewing black, with four dark red pattern. Pygophore which encloses two pairs of hook- like processes neighboring the hook shaped Aedeagus hook shaped, moderately thick, the blade bear four needle-like process. Some important body parts such asmouthparts, antenna, forewing and male genitalia were illustrated and drawn. Localities, date of collection and plant hosts were mentioned.